(untitled) (XXI Century. Spanish Literature and Culture)
This article analyzes the presence of various folktale motifs in one of the lesserknown, but unique novels, of the Valladolid writer Gustavo Martín Garzo, La princesa manca (1995). To do this, this article assesses the weighty impact of traditional folk tales on the formation of the author and his understanding of literature. Garzo Martín himself provides numerous examples of such an influence in a variety of articles published in periodicals, conferences, etc. Given this as its starting point, various aspects of La princesa manca are discussed with reference to recognizable folktale motifs that remain current in a contemporary work that updates them with new formulations and meaning.